The Organoleptic and Smoked Catfish Histology from Pre-cooking - Venny Yuliastri; Ruddy Suwandi; U. Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Catfish is one of the main commodities in fresh water aquaculture. Indonesia catfishproduction increased 37,49% in 2010 until 2014. Protein content of catfish is 17.7-26.7%and fat about 0.95 until 11.5%. The objective of this study was to determine the bestorganoleptic and to study the changes of tissue structure of catfish caused by process precookingand smoking process. Precooked Catfish with variation 5, 10 and 15 minute;temperature of 100oC, and smoked for 7 hours with a temperature of 90°C, analyzed inlaboratory. The results organoleptic consumers is the favored smoke catfish without anypre – cooking and catfish-results of pre-cooking for 5 minutes i.e. ten successive sense8.66; 7.66 smell 8.46; 7.8appearance 8.13;5.93 texture 6.86; 6.93. Organoleptic low on pre-cooked for 15 minutes the sense of 5.66 smell 7 appearance of 2.93 texture 5.53.Pre–cooked for 15 minutes has the highest water content of 26.33%. Pre–cooked for 5minutes with the lowest value of 16.23%. smoked catfish without any pre–cooking hasthe highest value of aw 0.82. Pre–cooked for 15 minutes had the lowest value of 0.78.Observation on histology showed fresh catfish the structure of the connective tissue stillcompact. Precooked catfish, myomer begins damage, catfish smoke without pre-cookingis characterized by the formation of fibrils wafy fibers are separated from one another andpre-cooking smoked catfish, myoseptum damaged and lead to the distance inter myomerbut myomer still intact.Keywords : Muscle, sensory analysis, water activity,water content